The role, readiness to change and training needs of the Athlete Health and Performance team members to safeguard athletes from interpersonal violence in sport: a mini review - Gillard, Allyson; Mountjoy, Margo; Vertommen, Tine; Radziszewski, Stephanie; Boudreault, Véronique; Durand-Bush, Natalie; Parent, Sylvie (Frontiers in Sports and Active Living, 2024)
Safeguarding athletes from interpersonal violence (IV) in sport is an important topic of concern. Athlete Health and Performance (AHP) team members working with athletes have a professional, ethical, and moral duty to protect the health of athletes, prevent IV, and intervene when it occurs. However, little is known on their respective roles regarding IV in sport and their needs to fulfill their responsibility of safeguarding athletes. The aim of this review is to synthesize knowledge about the roles, readiness to change and training needs of AHP team members to navigate IV in sport. A total of 43 articles are included in the review. Results show that all AHP team members have a role to play in safeguarding athletes and should therefore be trained in the area of IV in sport. Overall, very little research has directly assessed AHP team members' needs to positively foster safety and eliminate IV in sport. There are common training needs for all types of AHP team members such as the ability to recognize signs and symptoms of IV in sport. However, there are also specific needs based on the role of the AHP team members such as ways of facilitating behavioural change for sport managers. Findings from this review are mostly experts' recommendations and should therefore be interpreted as such. The results of the review can guide the development of future research and recommendations.